P‐4.6: Ultra‐high‐resolution Quantum Dots Color Converter with Notable Uniformity. (26th August 2021) - Li, Depeng; Ma, Jingrui; Liu, Pai; Wu, Zhenghui; Xu, Bing; Tang, Jing; Wang, Kai; Sun, Xiao Wei
Abstract : Using blue Micro‐LED back light and red‐green quantum dot (QD) color converter (QDCC) is a full color display technology with great potential to achieve high resolution, color purity and luminous efficiency. In this work, we try a new method of ligands exchange, using 3‐Mercaptopropionic acid (MPA) ligands with two functional groups to treat QDs in the liquid phase. The modified QDs can be sufficiently dispersed in the negative‐tone molecular resists. In our current process, the pixel size can be reduced to 5 fim and the large‐area ultra‐high‐resolution QDCC with great uniformity is realized.